On the burden of being in everyday life from the perspective of an auto-reflective experience of existential cares - Fabiś, Artur; Wąsiński, Arkadiusz (Old Age in the Stream of Life: Reflections on Old Age. Volume 2, 2019)
The paper is a report from qualitative research. It is an analysis of a narrative of a woman who presents her life in the perspective of existential concerns, including her spiritual life and thanatic fear she begins to experience in the old age. The narrator shows how, during her whole life, her life goals have been changing – which of them have become or remained important in the old age. Analysis of her life account reveals some mechanisms that help her look at her life in retrospect, and emphasis on the issue of suffering she has been constantly experiencing since childhood shows some constructive strategies of dealing with it. It is particularly evident in her struggle with loneliness.